2009
DOI: 10.1111/j.1399-5618.2009.00707.x
|View full text |Cite
|
Sign up to set email alerts
|

A critical appraisal of lithium’s efficacy and effectiveness: the last 60 years

Abstract: The history that depicts the evaluation of lithium's efficacy presents an interesting contrast: on the one hand, conviction that, of all psychotropic drugs, lithium has the best demonstrated efficacy; on the other hand, repeated attempts to question it. Those contesting lithium's stabilizing abilities have argued from several angles, for example that the proof was methodologically incorrect or insufficient, that the number of responders is small, or that the response is poor in practice and does not last. But … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 72 publications
0
55
0
Order By: Relevance
“…This episodic recurrent form of BD is known to be associated with an increased rate of recurrent mood disorders, but not schizophrenia in relatives, and a high response rate to long-term lithium, estimated at 80%. 13,14 A recent large prospective study 15 of patients with classical BD reported that the morbidity index in lithium-treated patients remained stable for up to 20 years. Moreover, lithium response was found to cluster in affected members.…”
Section: Natural History and Heterogeneity Of Bipolar Disordermentioning
confidence: 99%
“…This episodic recurrent form of BD is known to be associated with an increased rate of recurrent mood disorders, but not schizophrenia in relatives, and a high response rate to long-term lithium, estimated at 80%. 13,14 A recent large prospective study 15 of patients with classical BD reported that the morbidity index in lithium-treated patients remained stable for up to 20 years. Moreover, lithium response was found to cluster in affected members.…”
Section: Natural History and Heterogeneity Of Bipolar Disordermentioning
confidence: 99%
“…In the 1970s, lithium was the first drug approved in the USA as well as many other countries for the maintenance treatment of bipolar disorder. Although, since then, several other drugs have become available for the maintenance treatment of bipolar disorder (such as valproate, olanzapine, quetiapine, aripiprazole, and lamotrigine) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), lithium has remained a first-line option (12)(13)(14). This position was supported by a systematic review and meta-analysis of five randomized controlled trials (n = 770) that compared lithium with placebo in the maintenance treatment of bipolar disorder, excluding trials that randomly assigned patients who had been stable on longterm lithium to continue or discontinue lithium.…”
Section: Willem a Nolen A And Richard H Weisler Bcmentioning
confidence: 99%
“…Unfortunately, it has a narrow therapeutic window limited by adverse effects, 3,4 and neither the mechanism of action nor its associated toxicity are well understood. Lithium modulates multiple key cellular signaling molecules, 3,5 including inositol monophosphatase (IMPase) and glycogen synthase kinase-3 (GSK-3), considered likely to be therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%